MicroRNAs in Cardiovascular Regenerative Medicine: Directing Tissue Repair and Cellular Differentiation. (16th January 2013) - Sluijter, Joost P. G.
Abstract : MicroRNAs (miRNAs) are a class of short noncoding RNA molecules, approximately 22 nucleotides in length, which regulate gene expression through inhibition of the translation of target genes. It is now generally accepted that miRNAs guide processes and cellular functions through precise titration of gene dosage, not only for a single gene but also controlling the levels of a large cohort of gene products. miRNA expression is altered in cardiovascular disease and may thereby limit and impair cardiovascular repair responses. Increasing evidence of the essential role of miRNAs in the self-renewal and differentiation of stem cells suggests the opportunity of using the modulation of miRNA levels or their function in directing cell transplantation, cell behavior, and thereby organ healing. In this paper, an overview of miRNA biogenesis and their way of action and different roles that miRNAs play during the myocardial responses to injury and upon cell transplantation will be provided. We focused on cardiomyocyte survival, angiogenesis, extracellular matrix production, and how miRNAs can direct cell plasticity of injected cells and thus drive differentiation for cardiovascular phenotypes, including vascular differentiation and cardiomyocyte differentiation.